Tardive syndrome: An update and mini-review from the perspective of phenomenology. Issue 12 (21st September 2020) - Chen, Chun-Yu; Chiang, Han-Lin; Fuh, Jong-Ling
Abstract : Tardive syndrome (TS) is a group of movement disorders caused by the long-term use of dopamine receptor blocking agents. The phenotypic presentation of TS is diverse, ranging from the most well-characterized symptom of tardive dyskinesia to other symptoms, including dystonia, akathisia, myoclonus, parkinsonism, tremor, and tics. These tardive symptoms are distinct not only in their phenomenology but also in their clinical outcomes. However, our knowledge of the pathophysiology and management of TS is almost exclusively based on tardive dyskinesia. First-generation antipsychotics have a higher risk of inducing TS and have largely been replaced by second-generation antipsychotics with a lower risk of TS. However, patients with off-label use of second-generation antipsychotics are still at risk of developing TS. Thus, the management of TS remains a challenging and important issue for physicians. In this review, we update the information on the epidemiology, phenomenology, and treatment of TS from the perspective of the specific form of TS.